2ND Symposium on the application of vibration and noise in the diagnostic investigation of machines - PRZYBYLSKI, Józef (Archives of Acoustics, 1976)
The promotor of the Symposium was the Institute of Transport and Communications of Silesian Technical University in Katowice. Professor Ludwik MULLER was responsible for the scientific programme. 13 lectures were delivered and discussed by the following scientific centres: the Academy of Mining and Metallurgy, the Agricultural Academy in Lublin, the Technical Institute of the Air Force, the Institute of Motor Transport, the R & D Centre of the Katowice Metallurgical Plant, the R & D section of Zygmunt Metallurgical Plant, R & D section of a Small Capacity Car Factory, Silesian Technical University, gwilto. krzyski Technical University, Poznan Technical University, Warsaw. Technical University, the Naval College, the Engineering College in Zielona Gora, the Military College of Armour and Automotive Engineering, the Higher Officer Automotive College, and Agromet in Poznan. The symposium was greatly appreciated by the participants. During the main debate it was suggested that the Institute of Transport and Communications of the Silesian Technical University should organize scientific meetings devoted to the problems discussed.